Pengembangan Data Mart Keuangan untuk Organisasi Nirlaba - Sunjaya, Susiana; Filiana, Agata; Ernawati, Lussy; Virginia, Gloria (Maranatha University Press, 2024)
Finance is a critical component of organizational long-term viability. Non-profit organizations must pay close attention to their financial health. This is a form of accountability for funds entrusted to the organization by its stakeholders. Additionally, organizations must prepare for potential future financial risks. As a non-profit organization, SATUNAMA Foundation currently administers its financial data separately for each funding source. This complicates financial analysis and decision making, particularly when attempting to comprehend the organization’s financial health holistically. A financial data mart was built in order to assist data analysis as well as store historical data based on a predetermined set of analysis criteria. The Kimballs method and the starflake schema were used in the development of this data mart. The data mart was successfully implemented in accordance with the schema design and was able to fulfill the given analysis criteria. The data mart has fulfilled the four characteristics of data warehouse based on the data characteristic evaluation. From the operational perspective evaluation, data mart is proven faster than operational database thus making the data mart more efficient in providing information. Dashboard and pivot table are also successfully built to visualize the results.